Blaustein’s phenomenological psychology - Borek, Filip (Phainomena (Ljubljana), 2025)
The article explores the idea of psychology and phenomenology in Blaustein’s writings as well as its relation to two conceptions of phenomenology: Husserl’s and Stumpf ’s, respectively. The article is divided into five sections. In section 1, a historical background of the reception of Husserl’s and Stumpf ’s ideas in Blaustein is discussed. Section 2 concerns the conception of phenomenology in Husserl and in Stumpf regarding its subject matter. Section 3 discusses the ambivalent status of phenomenology in Blaustein’s theoretical project. Section 4 confronts Blaustein’s understanding of phenomenology with that of Husserl and of Stumpf. Section 5 summarizes the discussion of the similarities and differences between Blaustein, on the one hand, and Husserl and Stumpf, on the other hand. I argue that with regard to the question of the subject matter of phenomenology, Blaustein is closer to Husserl’s phenomenology rather than Stumpf ’s.
Keywords: Blaustein; fenomenologija; fenomenski svet; hiletika; Husserl; hyletics; phenomenal world; phenomenology; psihologija; psychology; Stumpf